S85 Analysis of blood cell counts as predictors of survival in patients with hypersensitivity pneumonitis versus idiopathic pulmonary fibrosis in a multicentre retrospective cohort. (12th November 2019) - Barratt, SL; Adamali, H; Creamer, A; Duckworth, A; Wollerton, R; Fallon, J; Gibbons, MA; Gooptu, B; Fidan, S; Nancarrow, T; Pepperell, J; Stone, RA; et al.
Abstract : Introduction: Hypersensitivity pneumonitis is a disease triggered by repeated inhalation and sensitisation to a variety of antigenic stimuli in susceptible individuals. It can be challenging to distinguish idiopathic pulmonary fibrosis (IPF) from fibrotic hypersensitivity pneumonitis (fHP). Predictors of disease progression are not well defined. Neutrophil:Lymphocyte ratio (NLR) and monocyte count have shown promise in providing prognostic value in IPF, but have not been examined in HP. Objectives: To further characterise a large, UK-based, multicentre, retrospective cohort of patients with HP to enable clinical phenotyping and investigation of factors that might predict survival. Methods: A multicentre evaluation of clinical data of IPF and HP patients presenting to the interstitial lung disease clinics at the North Bristol NHS Trust, University Hospitals of Leicester NHS Trust, Taunton and Somerset NHS Foundation Trust and the Royal Devon & Exeter NHS Foundation Trust was undertaken. All patients had received multidisciplinary team evaluation between 2005 and 2018. Mann-Whitney U tests and Kaplan Meier survival curve analysis were used as appropriate. Results: In a cohort of 493 IPF patients, the survival of patients with a high NLR was significantly lower than in those with a low NLR (median survival 36 months vs 62 months; Hazard Ratio (HR) 1.7, 95% C.I. 1.3–2.4, p=0.0002). NLR did not predict survival in a cohort of 182 HP patients. Monocyte count was statistically higher in IPF vs HP patients (median monocyte count 0.7 K/ul IPF n=408 vs 0.6 HP n=76 p=0.0051). For IPF only, monocyte count >0.95 K/ul predicted significantly poorer outcome (median survival 37 months vs 74 months; HR 2.0, 95% C.I. 1.3 – 3.2, p=0.0119); monocyte count was within normal range for the majority of HP patients. IPF patients also had significantly faster decline in both FVC and DLCO than HP patients (p=0.007 and 0.018, respectively). Conclusion: Further analysis of our fHP cohort has revealed that cellular biomarkers which may predict survival in IPF, namely Neutrophil:Lymphocyte ratio and monocyte count, do not significantly predict a poorer outcome in HP. More detailed interrogation of patient data may reveal other key baseline measures which will support clinical management.